A method for preparing a magnetic powder core for high-power power electronic equipment

By forming a thin layer of iron silicon and a silicon oxide coating with high resistivity on the surface of the iron powder, the problem of large eddy current and hysteresis losses in high-power power electronic equipment is solved, and a low-loss magnetic powder core is achieved.

CN115846658BActive Publication Date: 2025-03-14ANHUI RUIDE MAGNETOELECTRIC TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211561999.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-03-14
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The existing iron powder cores have large eddy current and hysteresis losses in high-power power electronic equipment, and resin coating cannot effectively solve these problems.

Method used

By mixing pure iron powder with substances such as γ-methacryloyloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, forming a surfactant liquid. After soaking and drying, a high-resistivity iron-silicon thin layer and a silicon oxide cladding layer are used to form a high-resistivity iron-silicon thin layer and a silicon oxide cladding layer to achieve high-resistivity insulation on the surface of the iron powder.

Benefits of technology

On the basis of retaining the high saturation magnetization of iron powder, the resistivity of the iron powder core is significantly improved, the eddy current and hysteresis loss is reduced, and the low-loss magnetic powder core is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The present invention provides a method for preparing a magnetic powder core for high-power power electronic equipment, and belongs to the technical field of magnetic materials. The specific operation is as follows: soak the metal iron powder in a mixed alcohol solution of γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, then mix the monosilane with silicon oxide powder and disperse them in an ethanol solution, and evenly spray them on the surface of the iron powder with an atomizing device, and through pressing and high-temperature annealing treatment, silicon penetrates into the surface of the iron powder to form a high-resistivity iron-silicon thin layer, while realizing the insulating coating of the iron powder by silicon oxide, thereby simultaneously realizing high saturation magnetization, high resistivity, and low loss in the iron powder core. Compared with the magnetic powder core prepared by the silicon oxide inorganic coating method, the saturation magnetization of the magnetic powder core prepared by the present invention is increased from 1.36T to 1.42T, and the resistivity is increased from 6.345×10 8 μΩ∙cm increased to 7.451×10 10 μΩ∙cm, the loss at 500Hz / 500mT is reduced by 37W / kg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a method for preparing a magnetic powder core for high-power power electronic equipment. Background Art

[0002] Iron powder cores are widely used in high-power power electronic equipment due to their high saturation magnetization. However, the resistivity of iron powder is low, resulting in large eddy current losses. In order to reduce the loss of iron powder cores, the powder core industry uses resin to insulate iron powder. Although it can partially reduce the eddy current between magnetic powders and reduce eddy current losses to a certain extent, due to the high viscosity of the resin, it is impossible to achieve completely uniform and effective insulation for all magnetic powders, so the overall eddy current loss of the powder core is still large. In addition, due to the addition of a large amount of resin, the magnetization paths between magnetic powders will be largely cut off, thereby increasing the structural demagnetization field inside the powder core and reducing the static magneto-coupling effect between magnetic powders, resulting in increased hysteresis losses. Obviously, resin coating cannot really solve the loss problem of iron powder cores. Therefore, how to achieve the reduction of eddy current and hysteresis losses as much as possible through high resistivity uniform coating while retaining the high saturation magnetization of iron powder is an urgent problem to be solved in order to achieve low loss in magnetic powder cores for high-power power electronic equipment. Summary of the invention

[0003] In order to improve the resistivity of a magnetic powder core for high-power power electronic equipment and reduce the loss, the present invention provides a method for preparing a magnetic powder core for high-power power electronic equipment.

[0004] The preparation steps of a magnetic powder core for high-power power electronic equipment are as follows:

[0005] (1) adding pure iron powder into a 98% ethanol solution at a mass ratio of 5:1 and uniformly stirring, ultrasonically cleaning to remove oil stains on the surface of the pure iron powder, and drying at 80°C to obtain clean pure iron powder;

[0006] (2) γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 3 to 5:1:6 to obtain a surfactant solution; clean pure iron powder is added to the surfactant solution in a mass ratio of 2:1 and soaked for 30 to 50 minutes, and completely dried in an oven to obtain activated pure iron powder;

[0007] (3) uniformly mixing monosilane and silicon oxide nanopowder at a mass ratio of 0.5 to 2:1000, dispersing the mixture in 200 g of 98% ethanol solution, spraying the mixture evenly on the surface of activated pure iron powder using an atomizing device, and completely drying the mixture in an oven to obtain treated pure iron powder;

[0008] (4) uniformly mixing the release agent, resin binder and treated pure iron powder, sieving, and pressing into a ring-shaped green body in a mold at a molding pressure of 1700 to 2100 MPa;

[0009] The mass ratio of the release agent to the treated pure iron powder is 5 to 6:1000, and the mass ratio of the resin binder to the treated pure iron powder is 1 to 2:1000;

[0010] (5) placing the annular green body into a heat treatment furnace, annealing it at high temperature in a nitrogen atmosphere, and cooling it with the furnace to obtain a finished magnetic powder core;

[0011] The performance index of the finished magnetic powder core is: the resistivity is 7.451×10 10 μΩ· cm, saturation magnetization is 1.42T; performance indicators tested by winding: under 1kHz / 1V conditions, relative magnetic permeability μ=62.8; loss: at 500Hz / 500mT, P cm =55W / kg, of which hysteresis loss is 34W / kg and eddy current loss is 21W / kg.

[0012] The further technical solution is as follows:

[0013] In the step (2), the drying condition is baking at 100-120° C. for 10-30 minutes.

[0014] In the step (3), the drying condition is baking at 80-100° C. for 10-30 minutes.

[0015] In the step (5), the high temperature annealing is first carried out at 200-300°C for 20-40 minutes, then the temperature is increased to 900-1100°C, kept at this temperature for 60-120 minutes, and then cooled in the furnace.

[0016] The beneficial technical effects of the present invention are embodied in the following aspects:

[0017] (1) The present invention utilizes the property that the resistivity of iron-silicon alloy is higher than that of pure iron, and utilizes silane to decompose at high temperature to diffuse silicon into the surface layer of iron powder. By controlling the amount of silicon source and the temperature of high-temperature annealing, siliconization is achieved only in the thin layer on the surface of the magnetic powder to form an iron-silicon thin layer. Under the premise of retaining the high saturation magnetization of the iron powder as much as possible, the surface resistivity of the iron powder can be increased, which helps to reduce eddy current loss. This process method is significantly different from directly replacing pure iron powder with iron-silicon magnetic powder, and can simultaneously achieve high saturation magnetization and high resistivity.

[0018] (2) The silane surfactant liquid configured in a special ratio in the present invention can effectively improve the surface activity of iron powder, which helps to promote the penetration and diffusion of silicon into the surface of iron powder at high temperature, thereby forming a uniform iron-silicon thin layer on the surface of iron powder. On this basis, the iron powder is then insulated and coated with silicon oxide, thereby forming a double-layer insulation of a high-resistivity iron-silicon thin layer and a higher-resistivity silicon oxide coating layer on the surface of the iron powder, effectively achieving insulation isolation between iron powders, greatly improving the resistivity of the iron powder core, and reducing the eddy current loss of the iron powder core.

[0019] (3) The present invention forms a thin layer of iron silicon with high resistivity on the surface of the iron powder, so that a high resistivity and low eddy current insulation effect can be achieved with a smaller amount of silicon oxide insulation coating. The reduction in the amount of silicon oxide helps the powder core to maintain a higher saturation magnetization intensity, while reducing the structural demagnetization field in the powder core and increasing the static magneto-coupling field between the magnetic powders, thereby effectively reducing the hysteresis loss and achieving low hysteresis loss and low eddy current loss in the powder core simultaneously.

[0020] (4) In the present invention, an iron powder core with a relative magnetic permeability level of 60 (±8%) is taken as an example. Sample No. 1 is prepared by a conventional silicon oxide inorganic insulation process, and sample No. 2 is prepared by the process of the present invention. The iron powder cores prepared by the two methods were tested for loss, saturation magnetization, and resistivity. The loss of the 500Hz / 500mT test was then fitted to separate the hysteresis loss and eddy current loss. Their comparative data are shown in Table 1.

[0021] Table 1

[0022]

[0023] As can be seen from Table 1, compared with the samples prepared by the conventional silicon oxide inorganic insulation process, the present invention forms a high-resistivity iron silicon insulation thin layer on the surface of the magnetic powder, so only a smaller amount of silicon oxide insulation coating is needed to achieve the same level of magnetic permeability, thereby achieving an increase in the overall saturation magnetization of the iron powder core and a reduction in hysteresis loss. At the same time, the double-layer insulation of the high-resistivity iron silicon thin layer and the higher-resistivity silicon oxide coating layer formed on the surface of the iron powder by the present invention greatly improves the resistivity of the iron powder core and effectively reduces eddy current loss. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with embodiments.

[0025] Example 1

[0026] The preparation steps of a high resistivity and low loss magnetic powder core for high power electronic equipment are as follows:

[0027] (1) Add 1000 g of pure iron powder to 200 g of 98% ethanol solution, stir evenly, perform ultrasonic cleaning to remove oil stains on the surface of the pure iron powder, and dry at 80°C to obtain clean pure iron powder;

[0028] (2) Mix 150g of γ-methacryloxypropyltrimethoxysilane, 50g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 300g of ethanol (mass ratio 3:1:6) to obtain 500g of surfactant solution. Add 1000g of clean pure iron powder to 500g of surfactant solution and soak for 30min; bake in an oven at 100℃ for 30min and completely dry to obtain activated pure iron powder;

[0029] (3) Disperse 0.5 g of monosilane and 0.5 g of silicon oxide powder in 200 g of 98% ethanol solution, mix well, spray evenly on the surface of activated pure iron powder using an atomizer, bake in an oven at 80°C for 30 min, and completely dry to obtain treated pure iron powder;

[0030] (4) 5 g of a release agent, 1 g of a resin binder, and 1000 g of treated pure iron powder (mass ratio 5:1:1000) were uniformly mixed, sieved, and pressed into a ring-shaped green body in a mold at a molding pressure of 1700 MPa;

[0031] (5) Place the annular green body into a heat treatment furnace and anneal it at high temperature in a nitrogen atmosphere, first keep it at 200°C for 20 minutes, then increase the temperature to 900°C and keep it at that temperature for 60 minutes, and cool it with the furnace to obtain a finished magnetic powder core;

[0032] The performance index of the finished magnetic powder core prepared in Example 1 is: the resistivity is 3.987×10 10 μΩ·cm, saturation magnetization is 1.43T; performance indicators tested by winding: under 1kHz / 1V conditions, relative magnetic permeability μ=94.5; loss: at 500Hz / 500mT, P cm =51W / kg, of which hysteresis loss is 27W / kg and eddy current loss is 24W / kg.

[0033] Example 2

[0034] The preparation steps of a high resistivity and low loss magnetic powder core for high power electronic equipment are as follows:

[0035] (1) Add 1000 g of pure iron powder to 200 g of 98% ethanol solution, stir evenly, and perform ultrasonic cleaning to remove oil stains on the surface of the pure iron powder; after cleaning, dry the pure iron powder at 80°C to obtain clean pure iron powder;

[0036] (2) Mix 181.5g of γ-methacryloxypropyltrimethoxysilane, 45.5g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 273g of ethanol (mass ratio 3.99:1:6) to obtain 500g of surfactant solution. Add 1000g of clean pure iron powder to 500g of surfactant solution and soak for 40min; bake in an oven at 110℃ for 20min and completely dry to obtain activated pure iron powder;

[0037] (3) 1 g of monosilane and 2 g of silicon oxide powder were mixed and dispersed in 200 g of 98% ethanol solution, mixed evenly, and sprayed evenly on the surface of activated pure iron powder using an atomizing device, and baked in an oven at 90° C. for 20 min to completely dry to obtain treated pure iron powder;

[0038] (4) 5.5 g of a release agent, 1.5 g of a resin binder, and 1000 g of treated pure iron powder (mass ratio 5.5:1.5:1000) were uniformly mixed, sieved, and pressed into a ring-shaped green body in a mold at a molding pressure of 1900 MPa;

[0039] (5) Place the annular green body into a heat treatment furnace and anneal it at high temperature in a nitrogen atmosphere, first at 250°C for 30 minutes, then increase the temperature to 1000°C and keep it for 90 minutes, and cool it with the furnace to obtain a finished magnetic powder core;

[0040] The performance index of the finished magnetic powder core prepared in Example 2 is: the resistivity is 5.987×10 10 μΩ·cm, saturation magnetization is 1.42T; performance indicators tested by winding: under 1kHz / 1V conditions, relative magnetic permeability μ=76.9; loss: at 500Hz / 500mT, P cm =53W / kg, of which hysteresis loss is 30W / kg and eddy current loss is 23W / kg.

[0041] Example 3

[0042] The preparation steps of a high resistivity and low loss magnetic powder core for high power electronic equipment are as follows:

[0043] (1) Add 1000 g of pure iron powder to 200 g of 98% ethanol solution, stir evenly, and perform ultrasonic cleaning to remove oil stains on the surface of the pure iron powder; after cleaning, dry the pure iron powder at 80°C to obtain clean pure iron powder;

[0044] (2) Mix 208g of γ-methacryloxypropyltrimethoxysilane, 42g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 250g of ethanol (mass ratio 5:1:6) to obtain 500g of surfactant solution. Add 1000g of clean pure iron powder to 500g of surfactant solution and soak for 50min; bake in an oven at 120℃ for 10min and completely dry to obtain activated pure iron powder;

[0045] (3) 2 g of monosilane and 3 g of silicon oxide powder were mixed and dispersed in 200 g of 98% ethanol solution, and evenly sprayed on the surface of activated pure iron powder using an atomizing device. The mixture was baked in an oven at 100 ° C for 10 min and completely dried to obtain treated pure iron powder.

[0046] (4) 6 g of a release agent, 2 g of a resin binder, and 1000 g of treated pure iron powder (mass ratio 6:2:1000) were uniformly mixed, sieved, and pressed into a ring-shaped green body in a mold at a molding pressure of 2100 MPa;

[0047] (5) Place the annular green body into a heat treatment furnace and anneal it at high temperature in a nitrogen atmosphere, first at 300°C for 40 minutes, then increase the temperature to 1100°C, keep it for 120 minutes, and cool it with the furnace to obtain a finished magnetic powder core;

[0048] The performance index of the finished magnetic powder core prepared in Example 3 is: the resistivity is 7.451×10 10 μΩ·cm, saturation magnetization is 1.42T; performance indicators tested by winding: under 1kHz / 1V conditions, relative magnetic permeability μ=62.8; loss: at 500Hz / 500mT, P cm =55W / kg, of which hysteresis loss is 34W / kg and eddy current loss is 21W / kg.

[0049] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any modification and equivalent changes made according to the method of the present invention still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a magnetic powder core for high-power power electronic equipment, characterized in that The steps are as follows: (1) adding pure iron powder into a 98% ethanol solution at a mass ratio of 5:1 and uniformly stirring, ultrasonically cleaning to remove oil stains on the surface of the pure iron powder, and drying at 80°C to obtain clean pure iron powder; (2) γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and ethanol are mixed uniformly in a mass ratio of 3 to 5:1:6 to obtain a surfactant solution; clean pure iron powder is added to the surfactant solution in a mass ratio of 2:1 and soaked for 30 to 50 minutes, and completely dried in an oven to obtain activated pure iron powder; the drying condition is baking at 100 to 120° C. for 10 to 30 minutes; (3) uniformly mixing monosilane and silicon oxide nanopowder at a mass ratio of 0.5 to 2:1000, dispersing the mixture in 200 g of 98% ethanol solution, spraying the mixture evenly on the surface of activated pure iron powder using an atomizing device, and completely drying the mixture in an oven to obtain treated pure iron powder; the drying condition is baking at 80 to 100° C. for 10 to 30 min; (4) uniformly mixing the release agent, resin binder and treated pure iron powder, sieving, and pressing into a ring-shaped green body in a mold at a molding pressure of 1700 to 2100 MPa; The mass ratio of the release agent to the treated pure iron powder is 5 to 6:1000, and the mass ratio of the resin binder to the treated pure iron powder is 1 to 2:1000; (5) placing the annular green body into a heat treatment furnace, annealing it at high temperature in a nitrogen atmosphere, and cooling it in the furnace to obtain a finished magnetic powder core; The performance index of the finished magnetic powder core is: the resistivity is 3.987×10 10 ~7.451×10 10 μΩ· cm, saturation magnetization is 1.42~1.43T; performance indicators tested by winding: under 1kHz / 1V conditions, relative magnetic permeability μ is 62.8~94.5; Loss: 500Hz / 500mT, P cm The high temperature annealing is as follows: first, keep warm at 200-300°C for 20-40 minutes, then increase the temperature to 900-1100°C, keep warm for 60-120 minutes, and cool with the furnace.

Citation Information

Patent Citations

  • Preparation method for improving resistivity and density of Fe-Si-Al soft magnetic powder core body at same time

    CN113369474A

  • Preparation method of low-loss soft magnetic composite material

    CN113539662A